Diagnostic performance of EBV DNA load testing for nasopharyngeal carcinoma in nasopharyngeal swab outperforms the approach in other specimens - Xue-Qi Li; Dong-Feng Lin; Yu-Cong Cai; Shang-Hang Xie; Ke-Na Lin; Hang-Ning Zhou; Zhi-Cong Wu; Jun-Ping Ye; Yi-Nan Peng; Zheng Ma; Ling Guo; Wei Lin; et al. (BMC Cancer)
Abstract Objective The DNA load of Epstein-Barr virus (EBV) can be detected in different types of specimens, however, the diagnostic performance across specimens hasn’t been systematically compared in an independent study. We compared their diagnostic performances within nasopharyngeal swab (NPS), plasma, and saliva head by head in the same population in the endemic region. Methods We recruited 150 newly diagnosed NPC patients and 150 non-NPC controls from two cancer centers during the 2020–2021 years in southern China. EBV DNA loads in NPS, plasma, and saliva were tested by quantitative PCR (qPCR). Meanwhile, two EBV serology antibodies of VCA-lgA and EBNA1-lgA were assessed by enzyme-linked immunosorbent assay (ELISA). Sensitivity and specificity were compared among the EBV DNA loads across specimens, as well as with the traditional screening marker of EBV antibody score. Finally, the diagnostic performances for NPC with the combinations of the EBV DNA load and the antibody score were evaluated. Results EBV DNA loads in the NPS and plasma were higher in cases, and we further evaluated the diagnostic performances for NPC. EBV DNA load in saliva had no difference in cases and controls, P = 0.84. EBV DNA load in NPS showed a sensitivity of 92.00% (95% CI: 86.44%-95.80%) and specificity of 98.67% (95% CI: 95.27%-99.84%) for NPC. Compared with EBV DNA load in NPS, the approach in plasma exhibited a lower sensitivity of 85.33% (95% CI: 78.64%-90.57%, P < 0.01) and the same specificity of 98.67% (95% CI: 95.27%-99.84%, P = 0.66). EBV antibody score demonstrated a sensitivity of 94.67% (95% CI: 89.76%-97.67%) and a specificity of 90.00% (95% CI: 84.04%-94.29%). The combination of the EBV DNA load in NPS with EBV antibody score improved the specificity to 99.33%, while maintaining the sensitivity of 88.67%. Conclusion We demonstrated that EBV DNA load in NPS could better discriminate NPC patients from controls than the approach in plasma. EBV DNA load in saliva had no value for NPC diagnosis. The combination of EBV DNA load in NPS with EBV antibody could further improve the specificity, while maintaining a rather good sensitivity for NPC diagnosis.